Collagen-VI Specific Primer Design Identification in Rats (Rattus norvegicus) Pancreas - Stujanna, Endin Nokik; Ningsih, Sri Suci; Avissa, Rizkyana; Ayu, Novi Putri; Nurussofa, Zahra; Djuarna, Dewi Jantika; Latifah, Rini; Sukarya, Wawang Setiawan (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2022)
Type 2 diabetes mellitus, the most common diabetes type characterized by hyperglycemia, is caused by abnormal secretion and activity of pancreatic insulin enzymes. The extracellular matrix (ECM) plays a vital role in keeping β pancreatic cells intact and undissociated. The ECM in the pancreas can play a role in influencing insulin function and production. The most abundant ECM in the pancreas is collagen type VI. Collagen type VI has an essential role in the survival of pancreatic islet cells, including pancreatic β cells. Nowadays, Polymerase Chain Reaction (PCR) technology is widely utilized for molecular biology analysis. One of the most critical factors for successful PCR is designing the correct specific PCR primers. The objective of this study was to design a specific primer for collagen VI in the pancreas of Rattus norvegicus. The primer was designed and analyzed using MEGA.11, primer three-plus, and primer-BLAST. Five primer pairs were analyzed based on the characteristics of primer length, product amplicon length, Tm value, GC percentage, and secondary structure. Primer pair 3 (F:5’-TGTTTGGCTTTGTCGCGGGC-3’ and R:5’-TTGTTGCTGCCGACACTGGC-3’); Col6a2 (F:5’-TGTGGTCAACAGGCTGGGCG-3’ and R:5’-TCTGGCGCCGGCTCTCTTTG-3’) were considered as the best primer for the Collagen VI expression detection from the pancreas of Rattus norvegicus, which produce amplicon about 250pb and 245pb, respectively.